Urgensi Pengaturan Kesehatan Mental dalam Sistem Keselamatan dan Kesehatan Kerja (K3) di Indonesia - Febriansyah , Achmad; Jingga, Adinda Zhara; Turang, Yohanes Ricky; Rizki, Reza Nur; Marcelino, Aldi (Journal of Industrial Relations Studies, 2026)
This study examines the adequacy of Indonesia’s labor regulations in protecting workers’ mental health within the national occupational safety and health (OSH) framework. The research aims to analyze whether current laws including the Manpower Act No. 13/2003, the Job Creation Law, and social security schemes such as BPJS Ketenagakerjaan and BPJS Kesehatan provide sufficient legal protection for mental health risks arising in the workplace. Using a normative juridical method supported by qualitative analysis of recent studies and policy documents, this study finds that Indonesia’s regulatory framework remains heavily focused on physical hazards while lacking explicit provisions on psychosocial risks such as stress, burnout, and excessive workload. The results show a significant legal gap between existing norms and the increasing cases of work-related mental disorders reported in recent years. BPJS Ketenagakerjaan has not recognized mental disorders as occupational diseases, and BPJS Kesehatan provides only general psychiatric services without specific coverage for work-related psychological conditions. The study concludes that Indonesia urgently needs a dedicated regulation on psychosocial OSH, setting clear standards for risk assessment, employer obligations, mental-health support services, and government supervision. Strengthening mental-health protection is essential to ensuring worker welfare, safety, and dignity amid evolving workplace demands